2014
DOI: 10.4236/oju.2014.45008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Results of TIPU Repair for Hypospadias with “Spongioplasty Alone” and “Spongioplasty with Dorsal Dartos Flap”

Abstract: Objective: The aim of our study was to compare the results of tubularized plate urethroplasty with interposing healthy tissue spongioplasty alone and spongioplasty with dorsal dartos flap to assess the role of dartos flap in prevention of fistulae. Patients and Methods: A retrospective study was performed on 80 patients, aged 4 months to 27 years who underwent hypospadias repair using the Snodgrass technique. The patients were assigned to two groups. In group I (40 patients) the neourethra was covered with spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Bhat et al reported 2 fistulae in a series of 40 patients of TIP urethroplasty using spongioplasty in addition to dartos flap coverage. 27 In the present study, we found 5 (14.28%) fistula among 35 patients using dartos flap plus spongioplasty in the TIP urethroplasty. However, Kocvara et al reported a higher complication rate (40%) using the spongiosal tissue for neourethral coverage of 37 patients.…”
Section: Discussionsupporting
confidence: 48%
“…Bhat et al reported 2 fistulae in a series of 40 patients of TIP urethroplasty using spongioplasty in addition to dartos flap coverage. 27 In the present study, we found 5 (14.28%) fistula among 35 patients using dartos flap plus spongioplasty in the TIP urethroplasty. However, Kocvara et al reported a higher complication rate (40%) using the spongiosal tissue for neourethral coverage of 37 patients.…”
Section: Discussionsupporting
confidence: 48%
“…The use of a waterproofing second cover for the neourethra is well documented in literature varying from corpus spongiosum, dartos-based flaps (ventral, dorsal, and scrotal dartos flaps) to TV which is known to decrease the incidence of fistula and breakdowns. [ 2 5 6 7 8 9 10 11 13 14 15 ] We reviewed studies which used a second vascular cover following TIP repair to see if the success rates were better.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown good results with Snodgrass technique, but the most common complication reported is urethrocutaneous fistula which forms >60% of all complications. [ 4 ] A second vascular cover on the tube such as spongiosum, dartos, or tunica vaginalis (TV) is known to minimize or avoid this complication[ 2 5 6 7 8 9 10 11 13 14 15 ] but which flap provides a better cover is still a matter of debate since decades because results have been conflicting with different results in the hands of different surgeons. The aim of our study is to present our experience with TIP urethroplasty using tunica, dorsal, and ventral dartos as second cover and see which had a better outcome.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Patients were discharged from the hospital in 8–10 days after removal of per urethral catheter in the series.…”
Section: Discussionmentioning
confidence: 99%
“…If urethral plate requires a superficial incision for tubularization; then, it is considered to be an average one, and when it requires a deep incision then urethral plate is considered as narrow. [12] Severity of hypospadias was decided by meatal location at the level of bifurcation of spongiosum after penile degloving.…”
Section: Methodsmentioning
confidence: 99%